2017
DOI: 10.1007/s10964-017-0775-4
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Conventions of Bullying Thresholds: Exploring Differences between Low and High Levels of Bully-Only, Victim-Only, and Bully-Victim Roles

Abstract: Using a commonly accepted threshold of 2 to 3 times per month as a marker of bullying-involvement from noninvolvement, approximately 30% of U.S. students report being a bully, victim, or both. Although variation in the frequency of involvement exists, infrequent engagement (less than 2 to 3 times a month) is generally considered noninvolved. However, the question remains: Do these differences have implications for behavioral health patterns, including substance use, depression and school connectedness? The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 48 publications
0
8
0
3
Order By: Relevance
“…Longitudinal studies have consistently shown that aggressor teenagers have suffered previous experiences of victimisation, although not necessarily at the hands of their peers (Martínez-Ferrer & Sattin, 2017;Sentse, Kretschmer, & Salmivalli, 2015). Further evaluation of these expressions of violence and victimisation in multiple contexts would provide a more in-depth understanding of the relationship between these two roles, and the underlying explanatory mechanisms (Garaigordobil & Martínez-Valderrey, 2016;Gómez-Ortiz, Romera-Félix, & Ortega-Ruiz, 2017;Zych, Beltrán-Catalán, Ortega-Ruiz, & Llorent, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have consistently shown that aggressor teenagers have suffered previous experiences of victimisation, although not necessarily at the hands of their peers (Martínez-Ferrer & Sattin, 2017;Sentse, Kretschmer, & Salmivalli, 2015). Further evaluation of these expressions of violence and victimisation in multiple contexts would provide a more in-depth understanding of the relationship between these two roles, and the underlying explanatory mechanisms (Garaigordobil & Martínez-Valderrey, 2016;Gómez-Ortiz, Romera-Félix, & Ortega-Ruiz, 2017;Zych, Beltrán-Catalán, Ortega-Ruiz, & Llorent, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…That is, bullying and bully-victimization are each associated with some of the same negative outcomes for adolescents. Studies of gender differences in prevalence of bullying involvement generally indicate boys have higher rates of bully-perpetration, while girls have higher rates of victimization (e.g., Perren & Hornung, 2005;Viljoen et al, 2005; but see Goldbach et al, 2018, that found no gender differences). Studies of gender differences in problems associated with bullying and bullying-victimization are limited, but suggest mixed results, with some studies finding greater risk for females (CDC, 2011;Luk et al, 2010;van der Wal et al, 2003) and others no gender differences (Goldbach et al, 2018;M.…”
Section: Involvement In Bullyingmentioning
confidence: 99%
“…An estimated 30% of students in the United States are involved in bullying (bullies, victims, or bully–victims; Nansel et al, 2001). Recently, Goldbach et al (2018) suggested this estimate is low due to imprecise measurement and found 70.9% of their sample were involved in some form of bullying and/or victimization (noted as bullying/victimization henceforth). The bullying role of the youth varies, including victim-only, bully-only, bully–victim, and neither bully nor victim.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors agree that it occurs more frequently in boys [22,28,29]. However, other studies have reported that girls suffer PV to a greater extent than boys [30,31].…”
Section: Victimizationmentioning
confidence: 99%